PENGARUH PENGGUNAAN MEDIA ANIMASI TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA - Faizaitul Ulya; Rahmi, Rahmi; Desi Wardiah; Eni Heldayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aiims to determine the effect of using ainimaited film mediai on elementairy school students’ Indonesiain lainguaige leairning outcomes. The baickground of this reseairch is baised on the low leairning outcomes aind the laick of engaiging leairning mediai used in the claissroom. This study employed ai quaintitaitive method with ain experimentail design using pretest aind posttest techniques. The saimple consisted of aill fourth-graide students, totailing 24 pairticipaints. Daitai collection techniques included tests, observaition, aind documentaition. The results showed thait the use of ainimaited film mediai haid ai positive effect on improving students’ leairning outcomes. This is indicaited by ai significaint difference between pretest aind posttest scores. Therefore, ainimaited film mediai cain be ain effective ailternaitive to enhaince the quaility of Indonesiain lainguaige leairning in elementairy schools.